Different decay of antibody response and VOC sensitivity in naïve and previously infected subjects at 15 weeks following vaccination with BNT162b2 - Siracusano, Gabriel; Ruggiero, Alessandra; Bisoffi, Zeno; Piubelli, Chiara; Carbonare, Luca Dalle; Valenti, Maria Teresa; Mayora-Neto, Martin; Temperton, Nigel; Lopalco, Lucia; Zipeto, Donato (Journal of translational medicine, 2022)
COVID-19 vaccines have demonstrated effectiveness in reducing SARS-CoV-2 mild and severe outcomes. In vaccinated subjects with SARS-CoV-2 history, RBD-specific IgG and pseudovirus neutralization titers were rapidly recalled by a single BTN162b2 vaccine dose to higher levels than those in naïve recipients after the second dose, irrespective of waning immunity. In this study, we inspected the long-term kinetic and neutralizing responses of S-specific IgG induced by two administrations of BTN162b2 vaccine in infection-naïve subjects and in subjects previously infected with SARS-CoV-2. Twenty-six naïve and 9 previously SARS-CoV-2 infected subjects during the second wave of the pandemic in Italy were enrolled for this study. The two groups had comparable demographic and clinical characteristics. By means of ELISA and pseudotyped-neutralization assays, we investigated the kinetics of developed IgG-RBD and their neutralizing activity against both the ancestral D614G and the SARS-CoV-2 variants of concern emerged later, respectively. The Wilcoxon matched pair signed rank test and the Kruskal-Wallis test with Dunn's correction for multiple comparison were applied when needed. Although after 15 weeks from vaccination IgG-RBD dropped in all participants, naïve subjects experienced a more dramatic decline than those with previous SARS-CoV-2 infection. Neutralizing antibodies remained higher in subjects with SARS-CoV-2 history and conferred broad-spectrum protection. These data suggest that hybrid immunity to SARS-CoV-2 has a relevant impact on the development of IgG-RBD upon vaccination. However, the rapid decay of vaccination-elicited antibodies highlights that the administration of a third dose is expected to boost the response and acquire high levels of cross-neutralizing antibodies.